Beauty : a retelling of the story of Beauty and the Beast - McKinley, Robin (Oxford : David Fickling Books, 2011)
Kind Beauty grows to love the Beast at whose castle she is compelled to stay and through her love releases him from the spell which had turned him from a handsome prince into an ugly beast.
8.0
Young Adult.
Young Adult
Keywords: Fairy tales; Folklore; Fairy tales; Folklore